EFFECTIVENESS OF PERINDOPRIL AND AMLODIPINE COMBINATION IN HYPERTENSIVES WITH COPD - O. N. Kryuchkova; E. A. Kostyukova; E. I. Lebed; E. A. Itskova; M. A. Zakharova; E. Yu. Turna (Российский кардиологический журнал, 2014)
Aim. To study efficacy of the standard combination of perindopril and amlodipine in target blood pressure levels achievement in COPD patients with AH.Material and methods. Totally 28 patients included 17 men and 11 women, mean age 51,42±1,45 y.o. with the COPD II-III stage established, with arterial hypertension II stage, 2 grade. In treatment we used fixed antihypertensive combination of ACE inhibitor and calcium channel blocker amlodipine. The values of “office BP” were measured, with ambulatory blood pressure monitoring and spirometry data. Results. After 30 days there was significant decrease of the mean “office BP” values, in 24 (85,7%) patients there was decrease of target BP. By ABPM data the decrease of mean clock-round, daytime and nocturnal BP values revealed. There was increase of the quantity of patients with physiological sleep pattern of BP from 5 to 12 (17,8% to 42,8%). Various dose regimens of perindopril/arginine combinations in 27 patients (96,4%) made it to achieve the BP level less than 140/90 mmHg. Long-term outcomes, tracked in the most of patients, showed good tolerability andhigh antihypertensive efficacy of the fixed perindopril and arginine combination.Conclusion. The use of fixed ACE inhibitor and calcium channel blocker combination fulfilled effective, dose dependent BP decrease and let most of COPD and AH patients reach the target BP. The treatment was followed by significant decrease of mean, daytime and nocturnal levels of ABPM. With the treatment there was recovery of physiological circle-round BP with reliable decrease at night. The possible side effect — dry cough — was rare and did not lead to the decrease of spirography parameters.